Critical care nurses' self-assessed patient observation skills: a cross-sectional survey study - Alastalo M.; Salminen L.; Jeon Y.; Vahlberg T.; Leino-Kilpi H. (Blackwell Publishing Ltd, 2022)
BACKGROUND:
Observing a patient's clinical condition is an important responsibility of critical care nurses and an essential component of their competence. Critical care nurses' patient observation skills contribute to patient safety and quality of care. These observation skills have not been assessed or measured previously.
AIM:
The aim of this study was to measure the self-assessed level of critical care nurses' patient observation skills and to explore the factors associated with these skills.
STUDY DESIGN:
This was a multicentre cross-sectional survey conducted in Finland.
METHODS:
The sample consisted of critical care nurses working at Finnish university hospitals. The data were collected between September 2017 and January 2018 using an instrument developed for the study - Patient Observation Skills in Critical Care Nursing (visual analogue scale 0-100). Descriptive and inferential statistics were used to analyse the data.
RESULTS:
A total of 372 critical care nurses (49%) responded. Finnish critical care nurses assessed their patient observation skills overall as excellent. The bio-physiological foundation was assessed as good, whereas skills in using observation methods and skills in recognizing changing clinical condition were assessed as excellent. Education for special tasks in intensive care units, information searching in scientific journals, working experience in critical care nursing and critical care nurses' perception of critical care as a preferred field of nursing were factors promoting patient observation skills.
CONCLUSIONS AND RELEVANCE TO CLINICAL PRACTICE:
The study provided a novel instrument for measuring critical care nurses' patient observation skills. The instrument may be used as an assessment tool in clinical practice and education. Developing orientation and on-the-job training in intensive care units are essential in assuring critical care nurses' adequate patient observation skills. Patient observation skills could be developed during nursing education by providing students with opportunities for clinical training and applying patient cases in virtual learning environments.